Influence of exchange-correlation functional on the structural and electronic properties of periodic structures with transition metal atoms - M. S. Baranava (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2022)
The influence of the exchange-correlation functional on the crystal fundamental property calculation is shown. CrGeTe3, compound with transition metals, was used for the simulation of structural and electronic properties. The calculations were carried out using such functional classes as LDA and GGA. It has been shown that LDA exhibits 0.4 % and 5.2 % overestimations of the lattice constants for a and c, respectively. GGA (OR) overestimates a by 0.58 % and underestimates c by 4 %. The influence of the Hubbard correction on the band gap was also investigated. If Ueff is applied to the d-electrons, then the band gap will decrease. This is due to the hybridization of the p-electrons of the chalcogen and the d-electrons of the transition metal. Thus, GGA demonstrates better agreement with the experiment. The convergence of the calculation of the total energy with a change in the k-points and the cutoff energy were also investigated.